Realizing Superior Redox Kinetics of Hollow Bimetallic Sulfide Nanoarchitectures by Defect‐Induced Manipulation toward Flexible Solid‐State Supercapacitors. Issue 5 (24th November 2021) - Liu, Shude; Kang, Ling; Hu, Jisong; Jung, Euigeol; Henzie, Joel; Alowasheeir, Azhar; Zhang, Jian; Miao, Ling; Yamauchi, Yusuke; Jun, Seong Chan
Abstract: As a typical battery‐type material, CuCo2 S4 is a promising candidate for supercapacitors due to the high theoretical specific capacity. However, its practical application is plagued by inherently sluggish ion diffusion kinetics and inferior electrical transport properties. Herein, sulfur vacancies are incorporated in CuCo2 S4 hollow nanoarchitectures (HNs) to accelerate redox reactivity. Experimental analyses and theoretical investigations uncover that the generated sulfur vacancies increase the active electron states, reduce the adsorption barriers of electrolyte ions, and enrich reactive redox species, thus achieving enhanced electrochemical performance. Consequently, the deficient CuCo2 S4 with optimized vacancy concentration presents a high specific capacity of 231 mAh g −1 at 1 A g −1, a ≈1.78 times increase compared to that of pristine CuCo2 S4, and exhibits a superior rate capability (73.8% capacity retention at 20 A g −1 ). Furthermore, flexible solid‐state asymmetric supercapacitor devices assembled with the deficient CuCo2 S4 HNs and VN nanosheets deliver a high energy density of 61.4 W h kg −1 at 750 W kg −1 . Under different bending states, the devices display exceptional mechanical flexibility with no obvious change in CV curves at 50 mV s −1 . These findings provide insights for regulating electrode reactivity of battery‐type materials through intentional nanoarchitectonics and vacancy engineering. Abstract : The fundamental research on CuCo2 S4 via intentional nanoarchitectonics and controllable vacancy engineering is proposed. Aided by experimental analysis and theoretical investigations, the improved electrochemical performance of deficient CuCo2 S4 hollow nanoarchitectures is attributable to the facilitated ion diffusion and charge transfer. Moreover, asymmetric supercapacitor devices with the deficient CuCo2 S4 exhibit high energy density and impressive flexibility.